Calculations of atomisation energy and singlet–triplet gap with iterative multireference configuration interaction. (3rd May 2022) - Fan, Jia-Qi; Zhang, Wen-Yan; Ren, Qing; Chen, Feiwu
Abstract : Iterative multireference configuration interaction (IMRCI) has been exploited to calculate the properties of small molecules. Atomisation energies of CH2 ( 1 A1 ), H2 O, HF, CH(X 2 Π), OH(X 2 Π) and CH2 ( 3 B1 ), and singlet–triplet separations of CH2, NH2 +, SiH2, and PH2 + are computed with MRCI and IMRCI. The accuracy of IMRCI is comparable to that of coupled-cluster singles, doubles, and perturbative triples (CCSD(T)), and better than that of MRCI. Singlet–triplet separations calculated with IMRCI are compared with the results of the second and third order Møller-Plesset perturbation theories, CCSD, CCSD(T), MRCI and FCI as well as experimental results. It is shown that the IMRCI method is both accurate and reliable. Moreover, the effect of the frozenness of the highest unoccupied molecular orbital (HUMO) on the IMRCI results is also investigated. It is demonstrated that the frozen HUMO approximation significantly lowers the computational cost of IMRCI with almost the same computational accuracy. GRAPHICAL ABSTRACT: UF0001